Optimasi Proses EDM Sinking Baja HMD5 di Mesin Makino Edaf3 Laboratorium Produksi Mesin dan Perkakas - Haris Setiawan; Wawa Wahyudin (Jurnal Pengelolaan Laboratorium Pendidikan, 2023)
The EDM sinking process is the process of cutting non-conventional workpieces by using electric sparks that occur when two electric poles are close together, the high temperature of the electric sparks can cause the workpiece particles are eroded and release to become burr in a very small size. The cutting rate in this process is influenced by many factors, including characteristics of the material, type of electrode, cutting parameters, condition of the coolant and method of spraying the coolant. This study aims to find optimum conditions for the EDM process with HMD5 steel workpieces, by using taguchi method wich is effective in making decisions with more than one variable. After all experiments and analysis, the results obtained are spark area level 1 or 50-75, current level 3 or 12A, pulse on time level 2 or 35 ms and pulse off time level 3 or 32 ms, which are the parameters with the most optimum material rete removal. After testing the optimazion result, MRR value increase from 20.26 mm3/min to 33.08 mm3/min and we have conclusion that the taguchi method can help to optimized parameter in EDM process.